Applied microfiber evanescent wave on ZnO nanorods coated glass surface towards temperature sensing - Jali, Mohd Hafiz; Rahim, Hazli Rafis Abdul; Md Ashadi, Md Johari; Thokchom, Siddharth; Harun, Sulaiman Wadi (Elsevier, 2018)
A temperature sensor fabricated by using silica microfiber laid on glass surface coated with Zinc Oxide (ZnO) nanorods is reported. The silica microfiber was tapered for waist of 5 μm using flame brushing technique. The glass surface was grown with ZnO nanorods using hydrothermal method. A significant response to temperature changes from 40 °C to 120 °C was observed due to the change of ZnO refractive index on the glass surface resulting different light attenuation in the silica microfiber. Sensitivity increases by a factor of 3.1 in microfiber laid on the coated glass surface as compared to uncoated glass surface. As the temperature increases, the output power of the ZnO nanorods coated glass surface has decreasing linearly from −19.8 dB m to −23.32 dB m with linearity and resolution of 99.8% and 1.75 °C respectively. The proposed temperature sensor employs the dispersion of evanescent wave from silica microfiber and glass surface coated with ZnO nanorods which is easier to handle during synthesis process and sensing applications.